An Analysis of Students' Speaking Fluency at XI Grade of MA KMM Kauman Padang Panjang - Annisa Aditya (Faculty of Education and Teacher Training of UIN Palopo, 2021)
The purposes of this study were to describe students’ fluency level and to identify students’ disfluency factors at MA KMM Kauman Padang Panjang. It employed quantitative research method with the class of grade XI students as the research population. There were 25 students taken as the research sample selected through purpossive sampling technique. The data were collected through speaking test and a set of questionnaire. In the speaking test, students were allowed to choose one of five topics provided and were asked to deliver short talks for 2 minutes. These short talks were recorded. In addition to the speaking test, there were 20 questions with four options as the answers. These questions represented five main factors of disfluency such as task with task difficulty, meaning focused, time pressure, planning and preparation, and task repetition. The collected data were mainly in the form of transcription texts mined from the recordings of the short talks as well as the answers from the questionnaire. The results of the study show that students’ fluency level at grade XI of MA KMM Kauman Padang Panjang is good (level 3). However, the information on disfluency which prevented them to get a higher score were also identified. Most of the main disfluency factors were task with task difficulty, meaningfocused, time pressure, planning and preparation, and task repetition.